The trajectory of changes in cognitive frailty and factors influencing it in elderly patients with cerebral infarction - Shengnan Xu; Qin Liang; Li Zhang; Shihua Liu (Guoji laonian yixue zazhi)
[Objective] The trajectory of cognitive frailty in elderly patients with cerebral infarction was analyzed, and the influencing factors were discussed. [ Methods] A total of 100 elderly patients with cerebral infarction hospitalized in Suzhou Hospital of Anhui Medical University from January to September in 2023 were selected for the study.Clinical data were collected on the patients, and cognitive frailty was assessed using the Frailty Screening Scale and the Montreal Cognitive Assessment Questionnaire (MoCA) at the time of admission and 1, 3, 6 months after treatment.Failty score ≥3 scores and MoCA <26 scores were defined as cognitive fraily.Potential categories of cognitive frailty change trajectories were identified by latent category growth modeling, and multifactorial logistic regression analyzed the factors influencing patients' cognitive frailty change trajectories. [ Results] The trajectory of cognitive frailty change in elderly patients with cerebral infarction identified by model fitting can be categorized into a group with a persistently low level of frailty (30 cases), a group with a slow rise in frailty (52 cases), and a group with a persistently high level of frailty (18 cases).Multifactorial logistic regression analysis showed that older age, poor sleep quality, and the number of comorbid chronic diseases > 4 were all risk factors for the development of persistent low levels of cognitive frailty into a slow rise in cognitive decline in elderly patients with cerebral infarction (P<0.05), Higher body mass index and high self-care ability were both protective factors for the development of persistent low levels of cognitive decline into a slow rise in cognitive decline in elderly patients with cerebral infarction (P<0.05).Older age, poor sleep quality and the number of comorbid chronic diseases >4 were risk factors for the progression of persistent low levels of cognitive decline to persistent high levels of cognitive decline in elderly patients with cerebral infarction (P < 0.05), and higher self-care ability were protective factors for the progression of persistent low levels of cognitive decline to persistent high levels of cognitive decline in elderly patients with cerebral infarction (P < 0.05). [Conclusion] Elderly patients with cerebral infarction can be divided into three trajectory types of cognitive decline changes, and there is group heterogeneity.